2001
DOI: 10.1006/jabr.2001.8782
|View full text |Cite
|
Sign up to set email alerts
|

Free Subgroups in Maximal Subgroups of GL1(D)

Abstract: Let D be a division algebra of finite dimension over its center F. Given a Ž .M contains a noncyclic free subgroup or there exists a maximal subfield K of D Ž . which is Galois over F such that K * is normal in M and MrK * ( Gal KrF . Using this result, it is shown in particular that if D is a noncrossed product division algebra, then M does not satisfy any group identity. ᮊ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…This result is used to prove that a maximal subgroup of A * can not be finitely generated. The reader may consult [7], and the references thereof for more recent results on multiplicative subgroups of A * . The object of this note is to investigate the algebraic structure of D when the F -linear hull F [M ] satisfies a polynomial identity.…”
mentioning
confidence: 99%
“…This result is used to prove that a maximal subgroup of A * can not be finitely generated. The reader may consult [7], and the references thereof for more recent results on multiplicative subgroups of A * . The object of this note is to investigate the algebraic structure of D when the F -linear hull F [M ] satisfies a polynomial identity.…”
mentioning
confidence: 99%
“…Thus, by Tits alternative, we know that G 1 is soluble-by-finite, i.e., there is a soluble normal subgroup N of G 1 such that G 1 /N is finite. Now, by [4,Lemma 3], N is abelian-by-finite. Thus, G 1 is abelian-by-finite.…”
Section: Corollarymentioning
confidence: 98%
“…Our next observation is about maximal subgroups of skew linear groups; these groups have been studied in a series of papers, see, e.g., [1,7,16,17]. In [7], it was shown that if D is an infinite division ring and m is a natural number, then every nilpotent maximal subgroup of GL m .D/ is abelian.…”
Section: Introductionmentioning
confidence: 99%